Epidemiological Characteristics and Their Influencing Factors Among Pulmonary Tuberculosis Patients With and Without Diabetes Mellitus: A Survey Study From Drug Resistance Surveillance in East China - Qian Wu; Min Wang; Yu Zhang; Wei Wang; Teng-Fei Ye; Kui Liu; Song-Hua Chen (Frontiers Media S.A., 2022)
BackgroundThe burden of pulmonary tuberculosis (TB) and diabetes mellitus (DM) have become serious global concerns, while the comprehensive evaluations of DM status and drug resistance in TB patients are still lacking.MethodsAll details of TB cases were collected from drug resistance monitoring sentinels in Zhejiang province. Fisher's exact test or Pearson chi-square test (χ2) was used to compare the baseline characteristics among TB with different DM statuses. The logistic regression model was used to estimate the relationship between DM and different drug resistance spectra. Univariate analysis and multivariate logistic model were used to explore the possible risk factors of drug resistance in TB patients with DM and no DM.Results936 TB cases with smear-positive in Zhejiang province were collected, in which 76 patients (8.12%) owned the co-morbidity of DM. TB-DM prevalence was higher in older, Han nationality, employed, accompanied by no health insurance and hepatitis B status. Among 860 cases of TB-no DM and 76 cases of TB-DM, drug resistance-TB accounted for 31.51% and 23.68% (P > 0.05), MR-TB accounted for 15.93% and 14.47% (P > 0.05), respectively. MDR-TB was 4.88% and 6.58% (P > 0.05). The incidence of poly-drug resistant tuberculosis (PDR-TB) in TB-no DM patients (10.70 vs. 2.63%, OR: 4.43; 95% CI, 1.07-18.36) was higher than that in the TB-DM group (P < 0.05). In univariate and multivariate analysis, none of the basic factors were statistically significant with drug resistance among TB-DM cases (all P > 0.05). Retreatment was the risk factor of drug resistance among TB-no DM cases.ConclusionsOur results showed that the drug resistance rate of the TB-DM group was not higher than that of the TB-no DM group. Patients with TB-no DM were at a higher risk for PDR-TB, but not for MDR-TB, MR-TB, and drug resistance-TB. Special attention should be paid to TB-no DM patients who have been previously treated. In the future, large-scale and well-designed prospective studies are needed to clarify the impact of DM on the drug-resistance among TB.